Barriers to timely treatment-seeking in patients with acute myocardial infarction in Malaysia: a qualitative study - Li, S. Chai; Zabidah, Putit; Sidiah, Siop (BioMed Central Ltd., 2016)
Background: Persisting delay in seeking treatment among Acute Myocardial Infarction (AMI) patients was reported in Malaysia despite intensified efforts in educating the public on symptoms of AMI and the importance of seeking prompt treatment. Studies outside Malaysia have shown that patients’ personal thoughts during symptom onset could contribute to the delay. The purpose of this study is to explore the barriers of AMI patients prior to the decision of seeking treatment in Malaysia. Methods: A qualitative descriptive research approach was chosen. Individual in-depth interviews were conducted among 18 patients with AMI. Data were analysed using thematic analysis. Recordings were transcribed and coded, codes were subsequently organized into categories. The stages of coding and identifying categories were repeated before themes were identified. Results: Three meaningful themes with nine sub-themes that may have influenced the delayed decision to seek treatment were identified. Some themes identified were culturally bound. Conclusions: The findings of this study give insights on barriers prior to the decision of seeking treatment when patients were experiencing AMI. Findings indicates that interventions targeted at increasing knowledge about AMI symptoms and correct actions using an informative approach at the current practice may not be adequate to reduce patient delay. The findings of this study could provide basis for the development of interventions that are culturally relevant to the Malaysians setting to promote behavioural change in the population and reduce pre-hospital delay.